Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888 - Sandes, Joana; Muricy, Guilherme; Pinheiro, Ulisses (Zootaxa, 2016)
The genus Scalarispongia was raised to gather species formerly allocated in Cacospongia with rectangular fibrous skeleton of cored primary fibers and uncored secondary fibers. Species of the genus Thorecta have a similar skeletal architecture, but the presence of a dermal armour distinguishes them from Scalarispongia. Here we describe two new species of Scalarispongia from northeastern Brazil and transfer Scalarispongia cincta to Thorecta cincta. Scalarispongia tubulata sp. nov. is thick encrusting to cushion-shaped, has tubular projections with thin walls, and surface irregularly microconulose. Scalarispongia cooki sp. nov. is massive lobate, with digitiform projections and irregular surface. Thorecta cincta n. comb. is pear-shaped with conulose surface, one large apical oscule and a belt of small oscula around the body. Its skeleton is composed by a regular and granular dermal armour and by a ladder-like network of concentrically laminated primary and secondary fibers. Cacospongia amorpha and Cacospongia levis are now the only species of the genus Cacospongia known to occur in the Brazillian coast, but both records need to be reassessed. A key to species of Thorectinae from the Tropical Western Atlantic is provided.